Platelet-Rich Plasma And Chronic Wounds: Remaining Fibronectin May Influence Matrix Remodeling And Regeneration Success - Moroz, Andrei[UNESP]; Deffune, Elenice [UNESP] (Elsevier, 2013)
Background: Platelet-rich plasma has been largely used as a therapeutic option for the treatment of chronic wounds of different etiologies. The enhanced regeneration observed after the use of platelet-rich plasma has been systematically attributed to the growth factors that are present inside platelets' granules. Aim: We hypothesize that the remaining plasma and platelet-bound fibronectin may act as a further bioactive protein in platelet-rich plasma preparations. Methods: Recent reports were analyzed and presented as direct evidences of this hypotheses. Results: Fibronectin may directly influence the extracellular matrix remodeling during wound repair. This effect is probably through matrix metalloproteinase expression, thus exerting an extra effect on chronic wound regeneration. Conclusions: Physicians should be well aware of the possible fibronectin-induced effects in their future endeavors with PRP in chronic wound treatment. © 2013 International Society for Cellular Therapy.
Keywords: Chronic wounds; Extracellular matrix; Fibronectin; MMP; Platelet-rich plasma; PRP; Wound regeneration